Financial Risk Management In The Creative Industry: A Case Study On Multimedia Companies In Indonesia - Leni Hartati; RR. Ella Evrita H (Cita Konsultindo Research Center, 2024)
Financial risk management in the creative industry, especially in multimedia companies in Indonesia, is important to maintain the sustainability and stability of the company. This research aims to identify the types of financial risks faced by multimedia companies, including liquidity, market, credit, and operational risks. The method used is a quantitative survey with questionnaires distributed to financial managers and related executives. The results show that multimedia companies often face high revenue volatility and reliance on projects, which increases liquidity and operational risks. Additionally, good risk disclosure can increase transparency and investor confidence. These findings provide insights for companies to adopt effective risk mitigation strategies to increase company value and competitiveness in the market.